Evaluation of drilling muds enhanced with modified starch for HPHT well applications (2020)
The use of carboxymethyl cellulose (CMC) in oil and gas well drilling operations has improved the filtration loss and mud cake properties of drilling muds. The introduction of starch has also reduced, for example, the viscosity, fluid loss, and mud cake properties of the drilling fluids. However, normal starch has some drawbacks such as low shear stress resistance, thermal decomposition, high retrogradation, and syneresis. Hence, starch modification, achieved through acetylation and carboxymethylation, has been introduced to overcome these limitations. In this study, modified starches, from cassava and maize, were used to enhance the properties of water-based muds under high-pressure high temperature (HPHT) conditions, and their performances were compared with that of the CMC. The mud samples added with acetylated cassava or maize starch exhibited the smallest filtrate volumes and filtrate losses within the American Petroleum Institute specification. Therefore, these modified starch-added muds could replace CMC as fluid loss agents since, unlike it, they can withstand HPHT conditions.